Presentation: Power and authority in the Andes - Judd Zanon, Esteban (1989)
In a broad and critical evaluation of the state of historiography around the subject of the peasantry, the historian Charles Walker poses in this issue of Allpanchis a series of challenges for the researcher in the Andean world. Among other deficiencies in the literature of recent years, Walker points out a strong tendency to present the peasant "as a normally apolitical subject who only knows how to react."